Diagnostic and prognostic value of disulfidptosis-related genes in sepsis - Wenlu Zou; Lintao Sai; Wen Sai; Li Song; Gang Wang (Infectious Medicine)
Background: Sepsis is a disease associated with high morbidity and mortality rates, especially among the elderly and patients in intensive care units. Disulfidptosis, a newly identified form of cell death triggered by disulfide stress, is emerging as a significant factor in disease progression. This study aimed to explore the diagnostic and prognostic value of disulfidptosis-related genes in sepsis. Methods: We obtained two datasets from the Gene Expression Omnibus (GEO) database to conduct our analysis. Functional enrichment analysis was performed to identify relevant biological pathways. A protein-protein interaction network was constructed to identify hub genes critical to sepsis. Additionally, we analyzed the immune infiltration status in sepsis patients. The diagnostic value of these hub genes for sepsis was evaluated using nomograms, receiver operating characteristic (ROC) curves, and calibration curves in both training and validation datasets. Finally, a miRNA-immune-related hub genes (miRNA-IHGs) regulatory network was developed to elucidate the synergistic interactions between miRNAs and their target genes. Results: A total of 3,469 differentially expressed genes (DEGs) were identified, of which seven were related to disulfidptosis (DR-DEGs). Functional enrichment analysis showed that DR-DEGs were significantly enriched in pathways related to actin dynamics. Five hub genes (MYH10, ACTN4, MYH9, FLNA, and IQGAP1) were identified as central to these processes. The analysis of immune infiltration revealed significantly lower levels of 11 immune cell types, while macrophages and regulatory T cells were significantly elevated in sepsis patients. The area under the ROC curves (AUCs) of the IHGs risk prediction model were 0.917 and 0.894 for the training and validation sets, respectively. A miRNA-IHGs regulatory network, comprising 17 nodes and 27 edges, was constructed, with MYH9 being the most frequently regulated by miRNAs. Conclusion: The pathophysiological process of sepsis appears to involve disulfidptosis, highlighting it as a potential new therapeutic targets for sepsis management.